Enhanced Electrochemical Performance of Li3V2(PO4)3/C Coated with Li Fast Ion Conductive Li7La3Zr2O12. Issue 7 (24th May 2017) - Cheng, Yarui; Li, Ruhong; Mu, Deying; Ren, Jie; Liu, Jianchao; Dai, Changsong
Abstract : Li7 La3 Zr2 O12 -coated Li3 V2 (PO4 )3 /C (LLZO-coated LVP/C) has been synthesized via a conventional sol-gel method, in which LLZO as the fast Li-ion conductor and carbon as the mixed coating with excellent electronic conductivity could enhance the transport of both electrons and Li-ions at the electrode's surface. X-ray diffraction (XRD) and transmission electron microscopy (TEM) with energy dispersive spectrometer (EDS) have been performed to prove the existence of LLZO on the surface of LVP. The valence states of the La and Zr elements are investigated by X-ray photoelectron spectroscopy (XPS). The capacity retention rates of LVP/C and LLZO-coated LVP/C after 100 cycles at 0.5C are 75.7% and 83.4%, respectively. Besides, the LLZO-coated LVP/C exhibits a specific discharge capacity of 161 mA h g −1 at 0.1C and 95 mA h g −1 at 5C at the voltage range of 3.0–4.8 V (vs Li + /Li), respectively. The superior electrochemical performance of LLZO-coated LVP/C can contribute to two aspects as follows: (1) LLZO coating provides a chemically stable layer which effectively reduces the chemical reactions between the active material and the electrolyte; (2) Compared with the uncoated LVP/C, the ionic conductivity of LLZO-coated LVP/C increases which is proved by the results of CV and GITT. Thus, we believe that the synthesis strategy of LLZO or other solid-state electrolytes and carbon hybrid coating could be employed to develop other cathode materials for their application in power lithium ion battery.